A novel ocular delivery of brinzolamide based on gellan gum: in vitro and in vivo evaluation - Sun J; Zhou Z (Dove Medical Press, 2018)
Jingfen Sun, Zhengshen Zhou Department of Ophthalmology, Ruijin Hospital, Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China Background: The aim of the study was to develop a sustained ocular delivery of brinzolamide (BLZ) based on gellan gum. Methods: The formulations were characterized for clarity, gelling capacity, rheological studies, pH, drug content, and in vitro drug-release behavior. In vivo rabbit eye irritation test was conducted to evaluate irritation of the BLZ gel drug-delivery system. The prepared BLZ formulations were then investigated in vivo and compared with commercially available BLZ eyedrops with regard to pharmacodynamics. Results: The results showed that the optimum concentration of gellan gum was 0.25% w/v; the prepared liquid was converted into a flowing gel after the addition of simulated tear fluid. In vitro release profiles showed that the release of BLZ from the in situ gel exhibited sustained characteristics. Draize test results showed that BLZ in situ gels did not stimulate signs of eye tissue activity and were less irritating than BLZ solutions and commercial Azopt. Conclusion: The results of pharmacodynamics implied that the novel preparation of BLZ in situ gel effectively prolonged the intraocular pressure-lowering effect after administration. Keywords: in situ gel, ion sensitive, glaucoma, ocular drug delivery, sustained release